Burden of non-motor symptoms in Parkinson’s disease and atypical parkinsonism syndromes: A single-center cross-sectional comparison study - Narendra Barad; Dnyaneshwar Asole; Mahendra Thakre; Charulata Sankhla (Annals of Movement Disorders, 2024)
BACKGROUND: Non motor symptoms (NMS) in idiopathic Parkinson’s disease (IPD) and atypical Parkinsonism (APD), are common. There are very few Indian studies addressing the frequency and burden in APD. Hence, this study aimed to investigate the frequency and burden of NMS in Indian patients with APD, compared with IPD and controls. OBJECTIVES: 1) To examine the clinical characteristics and burden of NMS in patients with APD, 2) To compare the frequency, and burden of NMS between typical and atypical Parkinsonism. METHODS: The study had total 114 participants, with 42 APD, 44 IPD patients meeting the standard diagnostic criteria and 28 age and sex matched healthy controls. The Non-Motor Symptoms scale (NMSS) was used to assess the frequency and burden of non-motor symptoms associated with parkinsonian disorders. RESULTS: The frequency and burden of NMS, across all domains, are highest (p < 0.05) in patients with atypical Parkinsonism compared to those with IPD and the control group. In the APD group, the most common NMS reported was sexual dysfunction (85%), followed by urinary urgency (72.5%), fatigue, lack of motivation, and nocturia (67.5%). The most common NMS reported in IPD patients were sexual dysfunction (81%), fatigue (70.45%), and constipation (68.18%). Restless legs symptoms were significantly more prevalent in the IPD group (p ≤ 0.05). The mean total NMS score was also significantly higher in APD patients (p ≤ 0.05). CONCLUSION: The frequency and burden of NMS, across all domains, are higher in patients with APD group.